The Marginal Cost of Public Funds is the Ratio of Mean Income to median Income - Dan Usher (Queen's University, Department of Economics, 2002)
The marginal cost of public funds is the equilibrium price at the intersection of the appropriately-defined demand curve for and the supply curve of public expenditure. In a world with identical people and with no excess burden of taxation, that price would have to be 1. Otherwise the median voter's choice of a demogrant - or of its opposite, a head tax - fixes the marginal cost of public funds at the ratio of the mean income to the median income. A proof of this assertion is presented not for its realism, but because it calls attention to the interaction of the different influences upon the marginal cost of public funds.
Keywords: H4; 330; Marginal Cost of Public Funds; Öffentliche Ausgaben; Opportunitätskosten; Pauschalbesteuerung; Medianwähler-Modell; Theorie; Grenzkosten